The Portrayal of Mood System and Love Language in Taylor Swift’s Lover Album - Widyaiswara, Tiara; Laili Qotrunnada Eka (Perkumpulan Dosen dan Pengajar Bahasa Inggris Se-Indonesia (ELITE Association Indonesia), 2025)
This study aims to analyze the interpersonal meaning in Taylor Swift's song lyrics in the Lover album, focusing on the mood system from Halliday's Systemic Functional Linguistics (SFL) theory and Gary Chapman's love language theory. A qualitative approach was used in this study, with discourse analysis of the song lyrics. Data collection techniques were conducted through documentation and literature study methods, in which the writer analyzed five selected song lyrics from Taylor Swift's Lover album. The data analysis technique used is the data analysis model of Miles and Huberman which includes data reduction, data presentation, and conclusion drawing. The results of the analysis show that declarative clauses dominate the song lyrics, which are used to convey personal feelings and experiences clearly and directly, thus strengthening the emotional message in the song. In the analysis of love language, Quality Time is the most dominant type of love language, followed by Words of Affirmation, Physical Touch, Acts of Service, and Receiving Gifts. The conclusion of this study shows that the combination of mood system and different types of love language in Taylor Swift's song lyrics creates complex and deep interpersonal meanings. The dominant declarative clauses clarify the expression of love and strengthen the emotional connection in the song, building a strong connection with the listener. These results show how Taylor Swift uses song lyrics to express feelings and build meaningful interpersonal relationships.